2020
DOI: 10.26710/sbsee.v2i1.1312
|View full text |Cite
|
Sign up to set email alerts
|

Attitude, Perceived Behavioral Control and Subjective Norms in Waste Segregation-at-Source Behavior: An Empirical Study

Abstract: Purpose: The aim of this paper is to assess the level and relationship between attitude, perceived behavioral control and subjective norms with waste segregation-at-source behavior among households in Putrajaya, Malaysia. Design/Methodology/Approach: A multi-stage sampling method used to obtain four hundred households in Putrajaya for the purpose of responding to the bilingual questionnaire. The quantitative data collected were analyzed using the IBM SPSS Version 26.0 software. Specifically, the descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
1
3
0
1
Order By: Relevance
“…Subjective norm, followed by attitude, is the most powerful predictor of behaviour change. Understanding and accepting social norms, especially the behaviour of family members, can help to adopt recycling behaviour [ 24 , 25 ]. We train children on the segregation practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjective norm, followed by attitude, is the most powerful predictor of behaviour change. Understanding and accepting social norms, especially the behaviour of family members, can help to adopt recycling behaviour [ 24 , 25 ]. We train children on the segregation practices.…”
Section: Discussionmentioning
confidence: 99%
“…Goal setting and goal attainment is crucial to achieving the objective [ 27 ]. It has been established that environmental views have a varying effect on environmental behaviour [ 24 ]. However, a favourable attitude toward waste separation at the source can increase participation in recycling programmes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lingappa et al (2020) found that the effects of family and peer influence on attitude towards entrepreneurship, subjective norms, and perceived behaviourial control are strong and positive. Moreover, perceived behavioural control highly influences households, while subjective norms moderately influence households (Cheng, 2020). Wijaya and Puspitowati (2021) observe that personal qualities, attitudes, subjective norms and self-efficacy affect entrepreneurial intentions.…”
Section: Introductionmentioning
confidence: 99%
“…Malaysians are generating approximately 33,000 tonnes of municipal solid waste per day with an average of 1.17kg per person per day (Lacovidou & Ng, 2020). Adequate and efficient municipal solid waste management is important in creating a 'zero waste' society (Cheng, 2020) and waste separation at source is one of the underlying elements in closing the loop of material, the Malaysian government has introduced the Separation at Source Initiative under Solid Waste and Public Cleansing Management Act 2007 (Act 672) in September 2015 that managed by the Solid Waste Management and Public Cleanliness Corporation (SWCorp) in cultivating households' waste separation behaviour. However, the effectiveness of the policy implementation and various programs of separation at waste and recycling are not significant in fostering waste separation at source practices and waste segregation still remained low among Malaysian households and not bringing observable improvement in municipal solid management practices.…”
Section: Introductionmentioning
confidence: 99%